Monitoring of milk production and total cholesterol concentration, gamma-glutamyltransferase, and glutathione peroxidase in Simmental cows blood - Terezija Silvija Marenjak; Darija Stipić; Nina Poljičak-Milas; Krešo Čolig (Mljekarstvo)
Milk production, total blood cholesterol concentration and activity ofgamma-glutamyl-transferase (GGT) and glutation peroxidase (GPx) in blood of Simmental cows was monitored during two control periods (first control period - May 2004; second control period - June 2004). The objective was to determine a relationship between milk production and particular blood parameters, and their possible implementation as an indicator of milk production. Twelve Simmental cows from small-scale dairy farm in Zagreb County were included in the study. Cows originated from the same herd andwere roughly of the same parity and stage of lactation. The average milk production and total blood cholesterol concentration were significantly higher in May then in June (20,55 L/d vs. 15,44 L/d; 4,55 mmol/L vs. 3,96 mmol/L, respectively), whereas the GPx and GGT activity was significantly lower in May in comparison with June (GPx=1720,66 U/L vs. GPx=1808 U/L, and GGT = 20,11 U/L vs. 23,22 U/L, respectively). A positive correlation between the milk production and the total blood cholesterol level was detected (r=0,58). The total blood cholesterol concentration in the blood plasma mighthave been one of the indicators of production performance in the Simmental cows herd, whereas the activity of stated enzymes may specify the nutritional status thereof the milk production depends on.